The prevalence of urinary incontinence following radical prostatectomy and its related factors: A national registry based study - Allameh, Farzad; Aliakbari, Fereshte; Nematollahi, Shahrzad; Dadpour, Mehdi; Ranjbar, Arash; Eslami, Mohammad Javad; Hosseini, Jalil; Ghanbari, Mohammad Ali (Archives of Men's Health, 2020)
Introduction: The purpose of this paper is to evaluate the prevalence and the risk factors of urinary incontinence following radical prostatectomy in Iranian population. This study is conducted based on the available data from the National Cancer Registry. Materials and Methods: In this retrospective study, we extracted the information of all the patients with organ-confined prostate cancer who underwent radical prostatectomy from 2010 to 2014. All the patients were interviewed face to face or via telephone to collect additional data. Urinary incontinence was evaluated by a questionnaire using the definition based on pads use. The effects of risk factors were evaluated using logistic regression models. Results: The details of 13,583 registered patients with prostate cancer were collected. Overall, the prevalence of urinary incontinence was estimated as 10.5% (n=1424). It is important to mention that the highest proportion of cases with urinary incontinence belonged to the age group of 71-80 years old (n=502, 35.2%), as well as patients with elementary education (n=458, 32%) or no education at all (n=333,23.5%). Furthermore, more cases lived in urban settings (n=1159,81.7%), one-fourth of them (n=365) smoked tobacco, and nearly 11% of them reported having been diagnosed with diabetes (n=152). The odds of having urinary incontinence increased by 20% in patients who had undergone radiotherapy as part of their treatment for prostate cancer (AOR=1.20, 95%CI: 1.07,1.36). Conclusion: We estimated the prevalence of urinary incontinence after radical prostatectomy as 10.5% among prostate cancer patients. We found that having been exposed to education, having been diagnosed with diabetes, and receiving radiotherapy, are amongst the significant risk factors for urinary incontinence. We also suggested that more predictor variables should be recorded in the National Cancer Registry.